GaN nanostructures for use in microelectronics - Bolat, R.; Alimzhanov, D.; Sugurbekova, G. (Nazarbayev University, 2013)
We have demonstrated possibility of replacing toxic and pyrophoric NH3, HCl by safer NH4Cl in the process of GaN synthesis. The method is flexible enough to produce thin films or bulk microrods. Good quality thin films were obtained at relatively low temperatures with high growth rate.
Keywords: first research week; microelectronics; GaN